2023
DOI: 10.36490/journal-jps.com.v6i1.1
|View full text |Cite
|
Sign up to set email alerts
|

KAJIAN KINETIKA PENENTUAN LAJU REAKSI PENETAPAN KADAR VITAMIN C PADA BROKOLI (Brassica oleracea L) DENGAN METODE TITRASI TITRIMETRI

Abstract: Latar belakang: Kerusakan brokoli disebabkan oleh beberapa factor yaitu mekanis dan biologis. Nilai kesegaran pada brokoli bisa diketahui dari laju respirasi, yang akan mempengaruhi susut berat, tekstur, kadar air, perubahan warna, kandungan vitamin C atau aktifitas fisiologis maupun mikrobiologis semakin meningkat. Metode studi kinetika reaksi oksidasi vitamin C dapat dilakukan melalui literature value, distribution turn over, distribution abuse test, consumer complaints, dan accelerated shelf-life testing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…At a hot temperature of 90°C the concentration was the lowest with an average content of 0.03092%. In general, the higher the reaction rate due to the influence of temperature, the higher the rate of degradation of vitamin C. So, there is an influence between temperature and the degradation of vitamin C. In research by Tambunan et al [20], temperature affects the speed of chemical reactions catalysed by an enzyme, at low temperatures the activity of the enzyme is inhibited and will maintain vitamin C. A decrease in vitamin C content has been observed in previous research, and the lowest vitamin concentration was found at the highest temperature treatment (90 °C), namely 0.02740% [2]. Meanwhile, in other studies, the highest concentration of vitamin C was at a temperature of 40°C and the lowest was at a temperature of 80°C.…”
Section: Experimental Design and Data Analysismentioning
confidence: 99%
“…At a hot temperature of 90°C the concentration was the lowest with an average content of 0.03092%. In general, the higher the reaction rate due to the influence of temperature, the higher the rate of degradation of vitamin C. So, there is an influence between temperature and the degradation of vitamin C. In research by Tambunan et al [20], temperature affects the speed of chemical reactions catalysed by an enzyme, at low temperatures the activity of the enzyme is inhibited and will maintain vitamin C. A decrease in vitamin C content has been observed in previous research, and the lowest vitamin concentration was found at the highest temperature treatment (90 °C), namely 0.02740% [2]. Meanwhile, in other studies, the highest concentration of vitamin C was at a temperature of 40°C and the lowest was at a temperature of 80°C.…”
Section: Experimental Design and Data Analysismentioning
confidence: 99%